Indirect fertility estimates of women with overseas Filipino worker and non-overseas Filipino worker spouses, differentials across selected variables - Del Mundo, Michael Dominic Chan (College of Social Sciences and Philosophy, University of the Philippines, 2015)
This study examines the relationship of Migration and Fertility in the Philippines by focusing on the effect of spousal separation due to international labor migration on fertility. The 2010 Census on Population and Housing data was used and the Brass P/F ratio method was utilized to estimate Total Fertility Rates (TFR) at the national and regional levels controlling for education and socio-economic status. Pooled Ordinary Least-Squares (OLS) regression was used to estimate the effect of spousal separation on fertility. Findings of the study reveal that Filipina women on the average give birth to approximately 3 children during their entire reproductive years. TFR estimates were low for women who have at least college education and who were classified in the higher wealth quintiles. Women with OFW spouses had a significantly lower fertility (TFR = 2.2) compared to women without OFW spouses (TFR = 3.0). Results of the regression analysis indicate that the TFR for women with OFW spouses is significantly lower than the TFR of women without OFW spouses. This finding suggests that spousal separation due to temporary international migration lowers fertility.